Quality of Strawberries at Low Temperatures Reviewed from Dyeing Time in Edible Coating Aloe Vera Gel and Storage Time - Luh Suriati; Anak Agung Sagung Manik Chindrawati; Ni Luh Putu Sulis Dewi Damayanti; I Putu Ajus Raditya Putra (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Strawberries are fruits with high economic value and are loved by the wider community. Its nutritional content is very high, but it has the weakness of being very easily damaged. One step to maintain strawberry quality and extend shelf life is to use an edible coating. This study aims to determine the effect of dyeing time on the edible coating of aloe vera gel on strawberry quality during cold storage. The plan used is the Complete Random Plan (RAL) with two factors and three repetitions. The first factor is the time strawberries are dipped in aloe vera gel, with 3 levels: 1, 2, and 3 minutes. The second factor is the storage time of strawberries dipped in aloe vera gel, with 3 levels: 0 days, 3 days, and 6 days at cold temperatures. Observations were carried out objectively, including: texture, pH, total dissolved solids, water content, and vitamin C. The best research results were obtained in the treatment time of dyeing strawberries into an edible coating of 1 minute and the storage time of strawberries at cold temperature for 3 days with a texture value of 3.95%, pH 3.39, total dissolved solids 4.00 °Brix, air 94,36%, dan vitamin C 41,29 mg/100 g. Contribution to Sustainable Development Goals (SDGs):SDG 2 – Zero Hunger: SDG 3 – Good Health and Well-BeingSDG 12 – Responsible Consumption and Production